PENGELOLAAN MUTU PENDIDIKAN DALAM PENGEMBANGAN MADRASAH TSANAWIYAH - Faizin Faizin (Nurul Jadid University, 2020)
Madrasah is Islamic educational institutions that are present in order to respond to the demands of the times. Since its establishment until now it has undergone a transformation, both in content and form. The development of positive characteristics, traditions and local wisdom (local power) continues through amputation, minimization and assimilation. This is inseparable from the principle that continues to be grasped, which is maintaining good old wisdom and taking or even creating new innovations that are relevant for progress. There is a polarization of education in Indonesia, between pesantren and public schools. Pesantren is the oldest Islamic education in Indonesia which until the 60s only focused on organizing religious education, in this case, mastery of the yellow book. Islamic boarding school is a model of traditional education that is firmly rooted in community traditions. At that time, pesantren were often considered unable to respond to the progress and demands of the times. On the other hand, there is general education (read: school) which focuses on non-religious subjects, religious studies are only around 2 hours a week. This fact gives the impression that public education (school) is a secular Dutch Indies heritage. In fact, many of the Muslim children who take general education. This has resulted in schools seen as unable to provide a balanced portion of faith and piety as well as science and technology.